Two-dimensional 67Zn HYSCORE spectroscopy reveals that a Zn-bacteriochlorophyll aP′ dimer is the primary donor (P840) in the type-1 reaction centers of Chloracidobacterium thermophilum. Issue 11 (10th March 2020) - Charles, Philip; Kalendra, Vidmantas; He, Zhihui; Khatami, Mohammad Hassan; Golbeck, John H.; van der Est, Art; Lakshmi, K. V.; Bryant, Donald A.
Abstract : Using pulsed EPR spectroscopy and isotopic labeling we demonstrate that reaction centers of Chloracidobacterium thermophilum have an unusual primary donor that is a dimer of Zn-bacteriochlorophyll a P ′ molecules. Abstract : Chloracidobacterium ( C .) thermophilum is a microaerophilic, chlorophototrophic species in the phylum Acidobacteria that uses homodimeric type-1 reaction centers (RC) to convert light energy into chemical energy using (bacterio)chlorophyll ((B)Chl) cofactors. Pigment analyses show that these RCs contain BChl a P, Chl a PD, and Zn 2+ -BChl a P ′ in the approximate ratio 7.1 : 5.4 : 1. However, the functional roles of these three different Chl species are not yet fully understood. It was recently demonstrated that Chl a PD is the primary electron acceptor. Because Zn 2+ -(B)Chl a P ′ is present at low abundance, it was suggested that the primary electron donor might be a dimer of Zn 2+ -BChl a P ′ molecules. In this study, we utilize isotopic enrichment and high-resolution two-dimensional (2D) 14 N and 67 Zn hyperfine sublevel correlation (HYSCORE) spectroscopy to demonstrate that the primary donor cation, P840 +, in the C . thermophilum RC is indeed a Zn 2+ -BChl a P ′ dimer. Density functional theory (DFT) calculations and the measured electron-nuclear hyperfine parameters of P840 + indicate that the electron spin density on P840 + is distributed nearly symmetrically over two Zn 2+ -(B)Chl a P ′ molecules as expected in a homodimeric RC. To our knowledge this is the only example of a photochemical RC in which the Chl molecules of the primary donor are metallated differently than those of the antenna.